Tinjauan Teologis Konsep Iman dan Perbuatan Bagi Keselamatan - Dessy Handayani (Sekolah Tinggi Teologi Torsina Surakarta, 2017)
The conflict between faith and actual action is caused by the ignorance of many people for grace and the law. The view that ‘faith is not enough' or 'faith must be parallel to deed' has completely ignored what the Word of God says about both. In this paper the author shows the standard of the Word of God to understand faith and deed takes place in the life of true Christianity. The life of faith must depart from faith and lead to faith, meaning we must live by faith. Faith is expressed through deeds. So, Faith and Actions are two things that can not be separated from each other, but complement each other. Salvation is the grace of God and Man can only accept salvation from God only through faith, not by works. Having received salvation in this way, man must work the salvation in life through the deeds that men do and do. If man is not active in salvation in this way after he becomes a believer, it shows that the faith he claims to be by mouth is dead faith. It's a sign that he has not really experienced salvation. Man is not saved by works. But deeds are a sign of whether the faith really lives. James does not intend to distinguish between faith and deeds; what is distinguished is between faith accompanied by deeds and faith which is not accompanied by deeds. For James faith must be accompanied by deeds. One can not exist without the other, for faith without works is dead.